Robust adaptive tracking control of underactuated ODINs under stochastic sea loads - Do, Khac Duc (Elsevier, 2014)
Although environmental loads induced by waves, wind, and ocean currents on marine vessels are naturally stochastic, all existing works on controlling these vehicles treat these loads as deterministic. This treatment deteriorates the control performance in a practical implementation. This paper presents a method to design controllers that force an underactuated omni-directional intelligent navigator (ODIN), a spherical underwater vehicle, to track a reference trajectory in two-dimensional space. Motivated by the vehicle's steering practice, the yaw angle regarded as a virtual control plus the surge thrust force are used to force the position of the vehicle to globally track its reference trajectory. The control design is based on several recent results developed for stability and control of stochastic systems, potential projection functions, and backstepping and Lyapunov's direct methods. Simulations are included to illustrate the effectiveness of the proposed results.